2017
DOI: 10.18632/oncotarget.22818
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-128 suppresses paclitaxel-resistant lung cancer by inhibiting MUC1-C and BMI-1 in cancer stem cells

Abstract: The existence of cancer stem cells (CSCs) is the main reason for failure of cancer treatment caused by drug resistance. Therefore, eradicating cancers by targeting CSCs remains a significant challenge. In the present study, because of the important role of BMI-1 proto-oncogene, polycomb ring finger (BMI-1) and C-terminal Mucin1 (MUC1-C) in tumor growth and maintenance of CSCs, we aimed to confirm that microRNA miR-128, as an inhibitor of BMI-1 and MUC1-C, could effectively suppress paclitaxel (PTX)-resistant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Due to the suppression of MUC1-C and BMI-1, the MEK/ERK, PI3K/Akt and Wingless (Wnt)/β-catenin pathways are downregulated, leading to a decrease of the CSC population and impaired chemoresistance to PTX. In short, miR-128 is one of the potential targets for lung cancer treatment [32].…”
Section: Mir-128mentioning
confidence: 99%
“…Due to the suppression of MUC1-C and BMI-1, the MEK/ERK, PI3K/Akt and Wingless (Wnt)/β-catenin pathways are downregulated, leading to a decrease of the CSC population and impaired chemoresistance to PTX. In short, miR-128 is one of the potential targets for lung cancer treatment [32].…”
Section: Mir-128mentioning
confidence: 99%
“…Although paclitaxel, so‐called taxol, has been used for chemotherapy in several cancers including ovarian cancer, breast cancer, lung cancer, Kaposi sarcoma, cervical cancer, and pancreatic cancer and cancer stem cells, its resistance in stem cells and side effects are still hot issues for effective cancer therapy. Hence, new combination therapy with paclitaxel is attractive to overcome its resistance and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is a natural anti‐tumour agent that widely used for the treatment of a variety of tumours, including ovarian cancer . Koh et al reported that miR‐128 suppressed cell proliferation, metastasis, self‐renewal, migration and invasive ability of paclitaxel‐resistant lung cancer stem cells via inhibiting BMI‐1 proto‐oncogene, polycomb ring finger (BMI‐1) and C‐terminal Mucin1 (MUC1‐C). A previous study showed that miR‐128 level was decreased in cisplatin‐resistant epithelial ovarian cancer SKOV‐3/CP cells compared with that in parental SKOV‐3 cells, and miR‐128 overexpression suppressed cisplatin resistance in SKOV‐3/CP cells .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has proven that miRNAs regulate thousands of cancer‐associated genes, thereby participating in cancer progression and suppression . miRNA‐128 (miR‐128) has been found to be involved in various cancers, such as gastric cancer, colorectal cancer, osteosarcoma, breast cancer and lung cancer . Recently, miR‐128 was found to be dysregulated in ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%